O milagre da juventude: uma análise linguística de exemplares de discurso publicitário da indústria antienvelhecimento - Barbosa, Sílvia; Ninitas, Mariana Silva (Revista da Associação Portuguesa de Linguística, 2021)
In this work, we aim to analyze how the cosmetic industry communicates the idea of aging and how it offers solutions for reversing this natural process, in the advertising speeches about face creams, aimed at the female audience. We built a corpus of 112 texts on cosmetic products, collected in beauty catalogs, websites of beauty brands and retail chains in the perfumery and cosmetics market, which have a set of texts in European Portuguese on the theme of “aging”. From a perspective of Lexical-Semantic analysis with contributions of the Discourse Analysis Pragmatics we tried to identify linguistic patterns to understand which discursive strategies were manipulated when advertising products promise to reverse the natural aging process. We observed that brands have products where the name is not always self-explanatory of the function it proposes and without great commitment to the possible solution, as aging and the respective physical marks are understood as the result of a process that the skin suffered and not the person.